Plant leaf wax biomarkers capture gradients in hydrogen isotopes of precipitation from the Andes and Amazon. (1st June 2016) - Feakins, Sarah J.; Bentley, Lisa Patrick; Salinas, Norma; Shenkin, Alexander; Blonder, Benjamin; Goldsmith, Gregory R.; Ponton, Camilo; Arvin, Lindsay J.; Wu, Mong Sin; Peters, Tom; West, A. Joshua; Martin, Roberta E.; et al.
Abstract: Plant leaf waxes have been found to record the hydrogen isotopic composition of precipitation and are thus used to reconstruct past climate. To assess how faithfully they record hydrological signals, we characterize leaf wax hydrogen isotopic compositions in forest canopy trees across a highly biodiverse, 3 km elevation range on the eastern flank of the Andes. We sampled the dominant tree species and assessed their relative abundance in the tree community. For each tree we collected xylem and leaf samples for analysis of plant water and plant leaf wax hydrogen isotopic compositions. In total, 176 individuals were sampled across 32 species and 5 forest plots that span the gradient. We find both xylem water and leaf wax δ D values of individuals correlate ( R 2 = 0.8 and R 2 = 0.3 respectively) with the isotopic composition of precipitation (with an elevation gradient of −21‰ km −1 ). Minimal leaf water enrichment means that leaf waxes are straightforward recorders of the isotopic composition of precipitation in wet climates. For these tropical forests we find the average fractionation between source water and leaf wax for C29 n -alkanes, −129 ± 2‰ (s.e.m., n = 136), to be indistinguishable from that of temperate moist forests. For C28 n -alkanoic acids the average fractionation is −121 ± 3‰ (s.e.m., n = 102). Sampling guided by community assembly within forest plots shows that integrated plant leaf wax hydrogen isotopic compositions faithfully record the gradient of isotopes in precipitation with elevation ( R 2 = 0.97 for n -alkanes and 0.60 for n -alkanoic acids). This calibration study supports the use of leaf waxes as recorders of the isotopic composition of precipitation in lowland tropical rainforest, tropical montane cloud forests and their sedimentary archives.